Investigations on the angle of directional hearing acuity - Niewiarowicz, M.; Czajka, J.; Hojan, E. (Archives of Acoustics, 2005)
This article presents results of investigations of the angle of directional hearing acuity (ADHA) as a measure of the spatial hearing ability. A modified method proposed by Zakrzewski has been used – ADHA values have been determined for azimuths in the horizontal plane at the height of the listener’s head. Application of different acoustic signals - sinusoidal signals (pure tones), 1/3 octave noise, and amplitude modulated 1/3 octave noise, helped to reveal significant differences in ADHA values for individual signal types. A better localization of the sound source for noise type signals than those for sinusoidal signals has been found. Furthermore, smaller differences in the perception of noise signals compared with differences in the perception of sinusoidal signals were recorded for individual listeners. The best localization was stated for the azimuth 0o and the worst for the azimuth 90o and 270o.